Quantitative and qualitative variables of semen from surubim do Iguaçu, Steindachneridion melanodermatum Garavello, 2005 (Siluriformes: Pimelodidae) - Sant’Anna, J. F. M.; Moraes-Neto, A.; Castro, J. P.; Sczepanski, T. S.; Pohv, J. A.; Lopera-Barrero, N.; Artoni, R. F. (Brazilian journal of biology, 2019)
Abstract The objective of the present work was to assess the qualitative and quantitative characteristics of semen from the surubim do Iguaçu (Steindachneridion melanodermatum). Induced spermiation was achieved in eleven males with mean weight of 1.76 ± 0.48 kg and average age of two years and semen was collected by stripping. The average volume was 1.34 ± 0.73 mL. The duration of sperm motility was 154.4 ± 72.6 and 149.0 ± 77.5 seconds after activation with hatchery water and distilled water, respectively. The sperm concentration estimated by hemocytometer was 5.423 ± 2.155 x 1010 spermatozoa/mL. The results indicate that S. melanodermatum semen is easily obtained during the spawning season and the seminal characteristics are adequate insemination and subsequent in vitro fertilization. Resumo O objetivo do presente trabalho foi avaliar características qualitativas e quantitativas do sêmen de surubim do Iguaçu (Steindachneridion melanodermatum). Para as análises, utilizaram-se onze machos com peso médio de 1,76±0,48 kg e idade média de dois anos, submetidos ao tratamento de hipofisação. O volume médio de sêmen coletado foi de 1,34 ± 0,73 mL. O tempo médio de motilidade dos espermatozoides após a coleta foi de 154,4 ± 72,6 e 149,0 ± 77,5 segundos para ativação com água do tanque e água destilada, respectivamente. Para a concentração espermática, a média foi de 5,423 ± 2,155 x1010 espermatozoides/mL. Os resultados indicam que o sêmen de S. melanodermatum é facilmente obtido no período reprodutivo analisado, e que as características seminais avaliadas são adequadas para reprodução induzida.